KEKERASAN TERHADAP ANAK DALAM RUMAH TANGGA DALAM NOVEL PINTU TERLARANG KARYA SEKAR AYU ASMARA - Syafridon Syafridon; Nurizzati Nurizzati; Bakhtaruddin Nasution (Faculty of Languages and Arts, Universitas Negeri Padang, 2014)
The purpose of this study is to describe violence againts children in the novel Pintu Terlarang by Sekar Ayu Asmara. In this novel, Pintu Terlarang, shows physical and psycological violence. This research data is a novel Pintu Terlarang by Sekar Ayu Asmara. The source of data in this study is the novel Pintu Terlarang by Sekar Ayu Asmara. This novel was published by Pt. Gramedia Pustaka Utama with the number of pages viii and 264 pages lenght of 20 cm and widht 19 cm in jakarta, Juli 2009. The techniques of data collection is done by reading the novel Pintu Terlarang and mark the special section on violence against the children. Theb result of this study shows that the child obuse both physically and psychologically. Physical violence is a pictures of violence hitting, kicking, that caused injury, paint or disability on the victim’s body thust cause death, while psycological violence is the behaviour shown to brutallize, insult and say hard work.